Metal-Controlled Magnetoresistance at Room Temperature in Single-Molecule Devices - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2017)
The appropriate choice of the transition metal complex and metal surface electronic structure opens the possibility to control the spin of the charge carriers through the resulting hybrid molecule/metal spinterface in a single-molecule electrical contact at room temperature. The single-molecule conductance of a Au/molecule/Ni junction can be switched by flipping the magnetization direction of the ferromagnetic electrode. The requirements of the molecule include not just the presence of unpaired electrons: the electronic configuration of the metal center has to provide occupied or empty orbitals that strongly interact with the junction metal electrodes and that are close in energy to their Fermi levels for one of the electronic spins only. The key ingredient for the metal surface is to provide an efficient spin texture induced by the spin-orbit coupling in the topological surface states that results in an efficient spin-dependent interaction with the orbitals of the molecule. The strong magnetoresistance effect found in this kind of single-molecule wire opens a new approach for the design of room-temperature nanoscale devices based on spin-polarized currents controlled at molecular level. © 2017 American Chemical Society.